2021
DOI: 10.1158/1055-9965.epi-21-0162
|View full text |Cite
|
Sign up to set email alerts
|

Genital Powder Use and Risk of Epithelial Ovarian Cancer in the Ovarian Cancer in Women of African Ancestry Consortium

Abstract: Background: Genital powder use is more common among African-American women; however, studies of genital powder use and ovarian cancer risk have been conducted predominantly in White populations, and histotype-specific analyses among African-American populations are limited. Methods: We used data from five studies in the Ovarian Cancer in Women of African Ancestry consortium. Participants included 620 African-American cases, 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…Pooled analyses or meta-analyses of case-control studies have produced odds ratios of 1.2-1.4. [33][34][35][36][37] The HR from a pooled analysis of prospective cohort studies 21 also indicated a positive, albeit small association (HR 5 1.08), and as previously noted, this effect estimate is likely biased toward the null because of nondifferential misclassification of exposure. This possibility is well illustrated by the Sister Study, where we previously reported 27% ever use of genital talc, 21 but here observe 40% ever use across a wider age range.…”
Section: Discussionmentioning
confidence: 55%
“…Pooled analyses or meta-analyses of case-control studies have produced odds ratios of 1.2-1.4. [33][34][35][36][37] The HR from a pooled analysis of prospective cohort studies 21 also indicated a positive, albeit small association (HR 5 1.08), and as previously noted, this effect estimate is likely biased toward the null because of nondifferential misclassification of exposure. This possibility is well illustrated by the Sister Study, where we previously reported 27% ever use of genital talc, 21 but here observe 40% ever use across a wider age range.…”
Section: Discussionmentioning
confidence: 55%
“…The use of intimate care products is a relatively common practice among women, with estimates of use in more than 50% in some populations. [1][2][3][4][5][6] Use of these products, including genital powder and douching, has been shown to vary across multiple factors including age, race, ethnicity, body size, and socioeconomic status. 3,4,7,8 These products are used for a variety of reasons including cleanliness, freshness, odor removal, and dryness of the genital region.…”
mentioning
confidence: 99%
“…Pooled analyses of case-control studies have shown estimates of 24%-32% higher ovarian cancer risk for ever compared with never use of genital powder, as well as the suggestion of higher risk with increasing number of lifetime applications. 2,5 However, cohort studies, which have less detailed data on powder exposure (leading to nondifferential misclassification), have provided more ambiguous results, with limited power to detect modest associations even when data are pooled across studies. [12][13][14][15] Thus, given these previously identified differences by study design, 16,17 additional methods are necessary to more clearly understand the impacts of this common exposure on gynecologic and hormone-associated cancer outcomes.…”
mentioning
confidence: 99%